(E)-N′-(1-(7-Hydroxy-2-Oxo-2H-Chromen-3-Yl) Ethylidene) Benzohydrazide, a Novel Synthesized Coumarin, Ameliorates Isoproterenol-Induced Myocardial Infarction in Rats through Attenuating Oxidative Stress, Inflammation, and Apoptosis. (6th March 2020) - Feriani, Anouar; Khdhiri, Emna; Tir, Meriam; Elmufti, Afoua; Tlili, Nizar; Hajji, Raouf; Ammar, Houcine; Allouche, Noureddine; Abid, Souhir; Ghazouani, Lakhdar; Mnafgui, Kais
Abstract : The present study was directed to investigate the effect of precotreatment with (E)-N ′ -(1-(7-hydroxy-2-oxo-2H-chromen-3-yl) ethylidene) benzohydrazide (7-hyd.HC), a novel potent synthesized coumarin, on isoproterenol- (ISO-) induced myocardial infarction (MI) in rats. The hydrazone compound was characterized by IR, 1D, and 2D NMR analyses. Experimental induction of MI in rats was established by ISO (85 mg/kg/day, s.c) for two consecutive days (6th and 7th days). 7-hyd.HC or sintrom was given for 7 days prior and simultaneous to ISO injection. 7-hyd.HC offered a cardiopreventive effect by preventing heart injury marker leakage (LDH, ALT, AST, CK-MB, and cTn-I) from cardiomyocytes and normalizing cardiac function and ECG pattern, as well as improving lipid profile (TC, TG, LDL-C, and HDL-C), which were altered by ISO administration. Moreover, 7-hyd.HC precotreatment significantly mitigated the oxidative stress biomarkers, as evidenced by the decrease of lipid peroxidation and the increased level of the myocardial GSH level together with the SOD, GSH-Px, and catalase activities. 7-hyd.HC inhibited the cardiac apoptosis by upregulating the expression of Bcl-2 and downregulating the expression of Bax and caspase-3 genes. In addition, 7-hyd.HC reduced the elevated fibrinogen rate and better prevented the myocardial necrosis and improved the interstitial edema and neutrophil infiltration than sintrom. Overall, 7-hyd.HC ameliorated the severity of ISO-induced myocardial infarction through improving the oxidative status, attenuating apoptosis, and reducing fibrinogen production. The 7-hyd.HC actions could be mediated by its antioxidant, antiapoptotic, and anti-inflammatory capacities.